The spatiality of men who go missing on a night out: Implications for risk assessment and search strategies. Issue 2 (20th January 2020) - Newiss, Geoff; Greatbatch, Ian
Abstract : Purpose: The purpose of this paper is to quantify the risk of fatality for men who are reported missing following a night out. Additionally, the paper aimed to develop search heuristics to inform the development of search strategies, through an examination of the key geographical points involved in these cases. Design/methodology/approach: Cases were identified, and data collected, from online media sources supplemented with a request to UK police forces and a search of the UK Missing Persons Unit database. In total, 96 cases which occurred over a five-and-a-half-year period in the UK were included. The study compares the profile of fatalities that result from disappearances occurring in different types of geographical area. Location data were georeferenced allowing Euclidean distances between geographical locations to be generated. Findings: In total, 60 per cent of disappearances lasting longer than 48 h resulted in fatality, rising to almost all cases after three days missing. In 89 per cent of cases bodies are recovered from water; 11 per cent on land after the individual died from a fall, hypothermia or a drugs overdose. Practical implications: Search strategies can be informed by a consideration of the type of area the person was socialising (high night-time economy through to rural areas) and the geography of subsequent sightings. Originality/value: In focusing on the specific circumstances of a disappearance rather than an individual's personal characteristics, the paper offers an innovative approach to understanding risk (i.e. what is the likelihood of a particular outcome occurring) and the development of heuristics for search strategies in missing person cases.